EVALUASI IMPLEMENTASI STANDAR PENILAIAN PADA SEKOLAH ALAM BOGOR BERDASARKAN MODEL EVALUASI PROVUS - Fauzia Wida (Jurnal Evaluasi Pendidikan, 2017)
The objective of this research is to describe the discrepancy occurring between definition, instalation, process, and product by using a standard criteria. The research was conducted based on Provus evaluation model (Discrepancy Evaluation Model). Data were collected by using interview, quetioner, observation, and document analysis. Data was analyzed by using descriptive qualitative method and campared with the standard criteria. The subjects of the research consisted of Teachers and Head Master at Sekolah Alam Bogor. The results of the research showed that: (1) definition aspects were categorized as low, (2) installation aspects were categorized as moderate, (3) process aspects were categorized as moderate, and (4) product aspects were categorized as good.